Evangelikalismus : Protestantské křesťanství přizpůsobené situaci náboženského pluralismu - Vojtíšek, Zdeněk (Lidé města, 2014)
In the course of the last two hundred years, evangelicalism has emerged as one of the most notable global phenomena. This study briefly mentions the notion of the term “evangelicalism” and its roots in pietism, puritanism, and revivalism. The main part of the study is devoted to the development of evangelicalism with special respect to its interaction with larger societies and to its differentiating. The rise and evolving of the four main branches of evangelicalism – the holiness movement, Pentecostalism, fundamentalism, and new evangelicalism – are outlined, and regarding Pentecostalism, two more streams – the charismatic and neo-charismatic movements – are distinguished. In the second and minor part of the study, the possible reasons of the relative success of evangelicalism in pluralist societies are discussed. The adjustment of evangelicalism to the conditions of pluralist societies has clearly had an impact on some other Christian and even Non Christian religious institutions, and may have helped them to survive or to gain in the conditions of contemporary world.